Design and Analysis of Double Integrating and Dead time Processes. Issue 1 (2022) - Sindhuja, P. Princes; Vijayan, V.; Panda, Atanu; Panda, Rames C.
Abstract: Presence of integrator and time delay in transfer functions of physical processes makes the system difficult to control by conventional methods. This paper proposes a novel design of a modified closed loop structure for double integrating plus dead time (DIPDT) processes based on the locus of perturbed relay system (LPRS). A control law has been proposed using LPRS technique which includes the transition or feedthrough matrix (D) for integrating process. The LPRS method provides good servo behaviour but it results in offset in presence of disturbance. Hence a novel modified control structure with a lead lag compensator is designed and the closed-loop performance is compared with that of existing example of the literature works of DIPDT for servo and regulatory responses. Comparison of performance error indices and percent overshoot (PO%) with that of the other existing works reveals the superiority of the proposed scheme.